A critical examination of the relationship among research, theory, and practice: Technology and reading instruction. (October 2018) - Yang, Xinyuan; Kuo, Li-Jen; Ji, Xuejun; McTigue, Erin
Abstract: Recent technological advancements have changed how literacy is perceived, and it is no longer confined to the interaction with print text. The evolving definition of literacy has been reflected in the increasing number of teachers who are incorporating technology into their reading instruction. However, less is known about the extent to which these technology-integrated instructional practices are supported by reading theories. The purpose of this study is to systematically review how technology has been implemented in reading instruction and to explore how transitions of instructional practice from traditional classrooms to digital settings have been grounded in reading theories. The present study reviewed articles published over the past twelve years in flagship practitioner journals to examine the connections and the gaps between theory and practice. Our review uncovered that technology has served in reading instruction primarily in three ways: 1) to increase reading motivation, 2) to present information in multi-modalities, and 3) to promote collaborative learning. Consistent with other domains of reading instruction, social theories were found to be the prominent theoretical bases supporting technology-integrated practices; dual-coding theory has also emerged in recent years as the theoretical basis for technology use in reading instruction. However, most of the theories were rarely referred explicitly. Implications for researchers and practitioners were provided based on the gaps between theory and practice revealed in the current review. Highlights: Exploring how technology is incorporated in K-12 reading instruction. Examining the connections between theory and practice. Social theories provided primary theoretical support for using technology. Gaps between theoretical support and instructional practice when using technology.